Analysis of Speech Acts in Dialogue: (The Analysis Study to the Eleventh Grade of SMK Setia Bhakti Kota Tangerang in Academic Year 2019-2020) - Wicaksono, Dhani Arief; Sukendra, Irmala; Fachrurozy, Achmad (Foremost Journal, 2021)
The research is a pragmatic study on speech acts and conversational implicatures performed by the student’s dialogue at the Eleventh Grade of SMK Setia Bhakti. This research is aimed at identifying and describing the kinds of speech acts focusing on the dialogues. This research descriptively employed a qualitative method with the researcher as the key instrument and the data sheets used as the secondary instruments. The researcher had the role of planning, collecting, analyzing, and reporting the research findings. The data were in the form of text dialogue according to subject material class, there are Offering and Suggestion and Invitation. The steps of collecting data were students making a dialogue based on the instruction. After being collected, the data were organized and analyzed based on Searle and Leech’s theory in the illocutionary act. The research reveals some findings. There are 5 kinds of illocutionary acts in speech acts that emerged from the students’ dialogue. They are declarative, representative, expressive, directive, and commisive. First, directive speech act as one of the forms declare. The second, subtypes of representative there are stating, informing, agreeing, arguing, explaining, describing, convincing, predicting, reporting, and stating an opinion. Third, subtypes of expressive are stated in the form of greeting, thanking, apologizing, complimenting, stating pleasure, accepting, considering, and stating surprise. Fourth, subtypes of the directive are expressed in the form of commanding, requesting, suggesting, inviting, questioning, and warning. Then fifth, subtypes of kinds of speech act is commisive which is expressed in the form there are promising and offering. Each strength of illocutionary acts is used based on the text of the situation. In some of its findings, the result of the analysis speech act in illocutionary which result of every kind shows percentage; declarative was 53%, representative 19%, expressive 59%, directive 66%, and commisive 41%. Based on the findings, the directive is the illocutionary act emerged by the dialogue of students which has the most finding of various forms. There are commanding, suggesting, requesting, inviting, warning, and questioning.